The Effect of Thermal Reduction on the Water Vapor Permeation in Graphene Oxide Membranes. Issue 8 (19th August 2014) - Andrikopoulos, Konstantinos S.; Bounos, Giannis; Tasis, Dimitrios; Sygellou, Lamprini; Drakopoulos, Vassilios; Voyiatzis, Georgios A.
<x xml:space="preserve">Abstract</x> In the present study, the influence of the thermal reduction on the water vapor transmission properties of thin graphene oxide (GO) membranes is evaluated. The macroscopically measured property of the Water Vapor Transmission Rate (WVTR) exhibits step like dependence contrary to the gradual microscopic structural alterations identified by several techniques (XPS, FTIR and XRD) applied in situ during the thermal annealing process. Three distinct regions of WVTR‐values associated with distinct interlayer distances i.e., >7.5 Å, ∼6 Å and <6 Å are essentially observed which may be compared to the findings of the recently reported first principle calculations. Our experimental results enable the understanding of the water vapor unimpeded transmission through the layers of the oxygen rich GO nanostructured membranes and consequently facilitate the design of functional membranes for separation applications.